ƯỚC TÍNH LƯỢNG PHÁT THẢI KHÍ METHANE TỪ NƯỚC THẢI SINH HOẠT TẠI HUYỆN LỆ THỦY, TỈNH QUẢNG BÌNH THEO HƯỚNG DẪN CỦA IPCC - Võ, Thị Nho (Trường Đại học Đà Lạt, 2023)
Domestic wastewater has a high organic content and is thus one cause of greenhouse gas emissions. This study focuses on the estimation and prediction of methane emissions from wastewater in Lethuy district from 2017 to 2020 using the guidance of the IPCC. The results show that methane emissions have increased from 2017 to 2020 along with the population growth of Lethuy district. In 2020, the methane emissions of the low, medium, and high scenarios were, respectively, 226,280 tons/year, 386,804 tons/year, and 532,132 tons/year. The review of emission scenarios shows that if 80% of Lethuy households using septic tanks change to aerobic tanks, the methane emissions will drop by 71%.